Detection of Haemagglutination–Inhibiting antibodies against human h1 and h3 Strains of influenza A Viruses in pigs in Ibadan, Nigeria (2010)
Agricultural and commercial activities have continued to bring people and pigs into regular, close contact in Ibadan, Nigeria. This study was therefore designed to investigate the transmission of human influenza viruses to pigs in Ibadan, using serological surveillance. Serum specimens were collected from ninety-one (91/199) apparently healthy, unvaccinated Landrace pigs at three locations within Ibadan from April to June, 2008. Two strains of human influenza virus A: A/Brisbane/59/2007 (H1N1) and A/Brisbane/10/2007 (H3N2) were used in Haemagglutination-Inhibition Assay for antibody detection. Prevalence of HI antibodies to the two subtypes was 90.1%. Antibodies to influenza A/Brisbane/ 59/2007 (H1N1) were significantly (P < 0.05) more prevalent (80.2%) than those of influenza A/Brisbane/10/2007 (H3N2) (51.6%). Titres of HI antibodies to influenza A/Brisbane/59/2007 [mean = 3331.5] were significantly higher (P < 0.05) than those of influenza A/Brisbane/10/2007 [mean = 2212.3]. This study shows that these pigs were exposed to human strains of influenza A(H1N1) and A(H3N2) either prior to or during this study. The implications of these high prevalence and antibody titres are discussed in relation to influenza virus infection among pig handlers in Ibadan, Nigeria. We recommend that periodic investigation of circulating strains of influenza viruses in pigs and humans who handle pigs regularly in Nigeria and molecular characterization of such isolates be carried out to ensure early detection of interspecies transmission and potential future pandemic strains.